(n - 3/8) * 8/35 + 2 2/7 = 2 2/5
(n - 3/8) * 8/35 = 2 2/5 - 2 2/7
(n - 3/8) * 8/35 = 2 14/35 - 2 10/35
(n - 3/8) * 8/35 = 2 4/35
n - 3/8 = 2 4/35 : 8/35
n - 3/8 = 74/35 * 35/8
n - 3/8 = 37/4
n - 3/8 = 9 1/4
n = 9 1/4 + 3/8
n = 9 2/8 + 3/8
n = 9 5/8
n = 77/8
(n - 3/8) * 8/35 + 2 2/7 = 2 2/5
(n - 3/8) * 8/35 = 2 2/5 - 2 2/7
(n - 3/8) * 8/35 = 2 14/35 - 2 10/35
(n - 3/8) * 8/35 = 2 4/35
n - 3/8 = 2 4/35 : 8/35
n - 3/8 = 74/35 * 35/8
n - 3/8 = 37/4
n - 3/8 = 9 1/4
n = 9 1/4 + 3/8
n = 9 2/8 + 3/8
n = 9 5/8
n = 77/8